Perlecan, A Multi-Functional, Cell-Instructive, Matrix-Stabilizing Proteoglycan With Roles in Tissue Development Has Relevance to Connective Tissue Repair and Regeneration - Hayes, Anthony J.; Farrugia, Brooke L.; Biose, Ifechukwude J.; Bix, Gregory J.; Melrose, James (Frontiers in Cell and Developmental Biology, 2022)
This review highlights the multifunctional properties of perlecan (HSPG2) and its potential roles in repair biology. Perlecan is ubiquitous, occurring in vascular, cartilaginous, adipose, lymphoreticular, bone and bone marrow stroma and in neural tissues. Perlecan has roles in angiogenesis, tissue development and extracellular matrix stabilization in mature weight bearing and tensional tissues. Perlecan contributes to mechanosensory properties in cartilage through pericellular interactions with fibrillin-1, type IV, V, VI and XI collagen and elastin. Perlecan domain I FGF, PDGF, VEGF and BMP interactions promote embryonic cellular proliferation, differentiation, and tissue development. Perlecan domain II, a LDLR-like domain interacts with lipids, Wnt and Hedgehog morphogens. Perlecan domain III binds FGF-7 and 18 and has roles in the secretion of perlecan. Perlecan domain IV, an immunoglobulin repeat domain, has cell attachment and matrix stabilizing properties. Perlecan domain V promotes tissue repair through interactions with VEGF, VEGF-R2 and α2β1 integrin. The perlecan domain-V LG1-LG2 and LG3 modules antagonize these interactions. Perlecan domain V promotes reconstitution of the blood brain barrier damaged by ischemic stroke, is neurogenic and promotes corneal repair. Perlecan-VEGF-VEGF-R2, perlecan-FGF-2 and perlecan-PDGF interactions promote angiogenesis and wound healing. Perlecan domain I, III and V mediated interactions with platelet factor-4 and megakaryocyte and platelet inhibitory receptor promote adhesion of cells to implants and scaffolds in vascular repair. With the availability of recombinant perlecan domains, potential applications are now emerging for perlecan in repair biology. Perlecan co-localization vascular elastin in the intima, acts as a blood shear-flow endothelial sensor that regulates blood volume and pressure has a similar role in canalicular fluid, regulating bone development and remodeling. This complements perlecan’s roles in growth plate cartilage and in endochondral ossification to form the appendicular and axial skeleton. Perlecan is thus a ubiquitous, multifunctional, and pleomorphic molecule of considerable biological importance. A greater understanding of its diverse biological roles and functional repertoires during tissue development, growth and disease will yield valuable insights into how this impressive proteoglycan could be utilized successfully in repair biology.